2015
DOI: 10.1038/ncomms7563
|View full text |Cite
|
Sign up to set email alerts
|

A graphene field-effect transistor as a molecule-specific probe of DNA nucleobases

Abstract: Fast and reliable DNA sequencing is a long-standing target in biomedical research. Recent advances in graphene-based electrical sensors have demonstrated their unprecedented sensitivity to adsorbed molecules, which holds great promise for label-free DNA sequencing technology. To date, the proposed sequencing approaches rely on the ability of graphene electric devices to probe molecular-specific interactions with a graphene surface. Here we experimentally demonstrate the use of graphene field-effect transistors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
85
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(91 citation statements)
references
References 56 publications
(80 reference statements)
6
85
0
Order By: Relevance
“…[22] GFETs were also capable of distinguishing the conductance signature upon adsorption of the four different DNA nucleobases due to the different interface dipole field. [97] The same study concluded that the sensing of single nucleotide with graphene is feasible even without DNA amplification (amplification of DNA showed a detection limit of 50 aM using Rolling Circle Amplification [100] ). Another possibility for graphene-based DNA sensors, [202] is to configure a graphene nanoribbon FET with a nanopore and to probe the subtle differences in the conductance as the negatively charged DNA molecules translocating through the nanopore.…”
Section: Gfet Glucose Dna and Protein Biosensorsmentioning
confidence: 96%
See 1 more Smart Citation
“…[22] GFETs were also capable of distinguishing the conductance signature upon adsorption of the four different DNA nucleobases due to the different interface dipole field. [97] The same study concluded that the sensing of single nucleotide with graphene is feasible even without DNA amplification (amplification of DNA showed a detection limit of 50 aM using Rolling Circle Amplification [100] ). Another possibility for graphene-based DNA sensors, [202] is to configure a graphene nanoribbon FET with a nanopore and to probe the subtle differences in the conductance as the negatively charged DNA molecules translocating through the nanopore.…”
Section: Gfet Glucose Dna and Protein Biosensorsmentioning
confidence: 96%
“…[12] The broad sensing potential of graphene can only be unlocked by the introduction of sensitizer (bio)molecules and structures, e.g. various inorganic groups, [23][24][25][81][82][83][84][85][86][87][88][89][90] organic or organometallic molecules, [37,[91][92][93][94][95][96] DNAs, [97][98][99][100][101] proteins, [102] peptides, [30,31,103,104] nanoparticles, [105,106,107] and 2D heterostructure. [51,52,61,108] These molecules are able to respond chemically or physically to their nearby environment, whose responses could then be transduced into an appreciable change in the conductivity of the carbon-based honeycomb scaffold.…”
Section: Meeting the Challenges In Chemical Functionalization Of Grapmentioning
confidence: 99%
“…In particular, atomically thin nanoribbons formed from these materials, as one‐dimensional nanotransistors, are predicted to provide single‐molecule sensitivity. Although nanoribbons are quite similar to nanotubes in morphology, numerous experimental and theoretical results have showed that the conductance of nanoribbons is mostly modulated by surface‐charge‐induced gating, rather than charge scattering, which is inevitable in SWNT devices. For example, planar molecules such as nucleobases or aromatic compounds interact with the surface of nanoribbons via π–π interaction.…”
Section: One‐dimensional Nanotransistors For Single‐molecule Detectionmentioning
confidence: 99%
“…Ambipolar field effect, high carrier mobility, low intrinsic electrical noise, mechanical strength, and flexibility collectively represent some of the advantages that make graphene a promising material for FET bio-sensing (31). First-generation graphene-based biosensors have been developed to successfully detect bacteria (32), glucose (33), protein (34), pH (35), and DNA (34,36).…”
Section: Significancementioning
confidence: 99%